2014
DOI: 10.1371/journal.pone.0107470
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Serum Levels of sCD26 for Surveillance in Colorectal Cancer Patients

Abstract: One of the main aims of the follow-up after curative resection of colorectal cancer is the early detection and treatment of tumor recurrence. We previously demonstrated decreased preoperative soluble CD26 (sCD26) levels in serum from colorectal cancer patients. We extended now the study to investigate if sCD26 levels in postoperative serum serve as marker of recurrence of the disease during surveillance. Soluble sCD26 was measured in pre- and postoperative serum samples of 43 patients with primary colorectal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Our previous reports indicated the potential usefulness of sCD26 as a biomarker for colorectal cancer, particularly in early diagnosis [5][6][7] and follow-up [8]. In the latter case, increased levels could be valuable for the early detection of local and distant recurrence [8], perhaps related to the presence of CD26-expressing CSCs [8,9].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 97%
See 2 more Smart Citations
“…Our previous reports indicated the potential usefulness of sCD26 as a biomarker for colorectal cancer, particularly in early diagnosis [5][6][7] and follow-up [8]. In the latter case, increased levels could be valuable for the early detection of local and distant recurrence [8], perhaps related to the presence of CD26-expressing CSCs [8,9].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 97%
“…Serum levels of soluble CD26 (sCD26) and its dipeptidyl peptidase activity (DPP-IV) have been proposed as biomarkers for lung and colorectal cancer screening including metastasis detection [5][6][7][8][9]. A pilot study was designed to check their potential for ocular cancer detection.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Also serum CD26 is substantially dysregulated in various cancers: serum CD26 levels are increased in patients with hepatic cancer and decreased in patients with blood, thyroid and oral cancers [10,11]. Recently, CD26 has been identified as a serum marker for colorectal cancer detection and prognostic factor [12][13][14] while to best of our knowledge no study investigated the role of serum CD26 in presence of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, serum DPP4 levels is increased in patients with hepatic cancer and decreased in patients with blood, solid and oral cancer [10,11]. Recently, CD26 has been identified as a serum marker for colorectal cancer detection [11][12][13] as well as a prognostic factor able to promote human colorectal cancer metastasis [14], while to best of our knowledge no study investigated the role of serum CD26 in gastric cancer. Only a previous study suggested that CD26 expression level in surgical samples may be considered a reliable biomarker of malignant GISTs of the stomach characterized by distinct clinical, genetic, and histopathological features [15].…”
Section: Introductionmentioning
confidence: 99%